Impatiens jacobdevlasii (Balsaminaceae), a new species from Knuckles massif of Sri Lanka - Bandara, Champika; Herath, Sanath Bandara; Gopallawa, Bhathiya; Attanayake, Achala (Phytotaxa, 2022)
Impatiens jacobdevlasii Herath, C. Bandara & Gopallawa sp. nov. (Balsaminaceae), a new species from Knuckles (Dumbara) massif of Sri Lanka is described and illustrated. The detailed morphological characters, diagnostic comparisons, notes on habitat and ecology are presented. According to the IUCN Red List Categories and Criteria, I. jacobdevlasii is assessed as Critically Endangered (CR) by virtue of its limited distribution range and decline of mature individuals.